Assessment of sustained effects of levosimendan on right ventricular systolic functions in patients with advanced heart failure. Issue 4 (1st August 2016) - Mansiroglu, Asli Kurtar; Oner, Ender; Erturk, Mehmet; Karakurt, Huseyin; Somuncu, Mustafa Umut; Birant, Ali; Kalkan, Ali Kemal; Ozturk, Derya; Eksik, Abdurrahman
Abstract : Background Poor right ventricular function is an independent prognostic marker for mortality in heart failure patients. Echocardiographic studies concerning effects of levosimendan on right ventricular function performed second measurements just after or 24 hours after levosimendan infusion. We aimed to detect sustained effects of levosimendan infusion on right ventricular systolic function. Method The study consisted of 47 patients with acutely decompensated heart failure with NYHA class III or IV symptoms. Levosimendan was infused for 24 hours. Before and 5 days after the initiation of infusions, functional class was assessed, NT-proBNP levels and LVEF, RVEF, using tissue Doppler imaging, RV isovolumic myocardial acceleraton (IVA), peak myocardial velocity during isovolumic contraction (IVV), peak systolic velocity during ejection period (Sa), early (E') and late (A') diastolic velocities, and E'/A' ratio were measured. Results NYHA class improved and NT-proBNP levels were significantly reduced. LVEF and RVEF also improved significantly. Tissue Doppler-derived systolic indices of IVV and IVA increased and RV diastolic indices improved. Conclusion Improvements in RV systolic and diastolic functions continue after levosimendan infusion as expressed by conventional echocardiographic and TDI-derived parameters in patients with acute decompensated HF.